Value Intentions in Future Art Teachers’ Professional Training - Rebrova, Olena Yevhenivna; Oleksiuk, Olga Mykolaivna; Batiuk, Nataliia Orestivna; Rebrova, Hanna Oleksandrivna (Journal of History Culture and Art Research, 2020)
The article is devoted to the study of future art teachers’ value sphere. A wide range of applications of the theory of values in various fields of knowledge is shown: culturology, psychology, pedagogy, art education, economics; classification of values in science is given. A number of issues is actualized, concerning values in the context of cultural development and at the same time global crises; professional development, competitiveness and life views and needs; development of person’s abilities and his/her self-realization in art creativity. The artistic-communicative, professional-hermeneutic and motivational-need spheres in the future art teachers’ creative self-realization are singled out. These areas are subject to pedagogical influence, while becoming a conglomeration of value intentions of the individual. Theoretical substantiation is conducted and the essence of the phenomenon of future art teachers’ value intentions is determined, which combines the specified multi-vector values. The meaning of the terms “intentionality” and “intentions” is clarified. Emphasis is placed on the importance of value intentions of the individual in the economic projection and compliance of this socio-personal construct with the current concept of student-centered learning. The results of the study of future art teachers’ value intentions, which are formed during professional training and creative activity, are given. The results of the value intentions diagnostics and dynamics of their changes in accordance with future musical art teachers’ professional training are highlighted. Scientific approaches and technologies that effectively influence their value intentions are outlined. It is proved that definition of a conglomeration of value intentions of an individual allows a qualitative choice of methods for the formation of creative and competitive personality of future musical art teachers and teachers of art disciplines in general.